Postharvest handling practices on selected local fruits and vegetables at different levels of the distribution chain. - Osman, Azizah; Saari, Nazamid; Saleh, Rosli; Bakar, Jamilah; Zainal, Noor Diana; Yacob, Masturina (Federal Agricultural Marketing Authority (FAMA), 2009)
Proper post harvest handling practices are important to reduce post harvest losses and improve overall harvest quality. However, inevitable post harvest losses occur during post harvest handling at different levels of the distribution chain. A survey was conducted at different levels of the distribution chain where 634 respondents were surveyed from various zones to identify post harvest handling activities that were practised, the potential post harvest activities that can be carried out, and the factors contributing to post harvest losses. The results showed that 27% of fruits and vegetables were sent directly to the wholesaler without any post harvest handling activities. The remaining was weighed (25%), packed (17%) and washed (10%). Among the post harvest handling activities, packaging (23.8%) had the highest potential of reducing post harvest losses. A majority of the farmers did not perform potential post harvest handling activities mainly because of insufficient knowledge. As for the four categories (knowledge, attitude, infrastructure and resources) identified contributing to post harvest losses, the results showed that 36.7% was due to insufficient knowledge of good handling practices, 50.3% due to inefficient/improper handling systems, 51.9% due to improper infrastructure and 38.8% due to insufficient funding.